Modeling Confinement in Analogy with Black Holes - Gamboa-Rios, J (World Scientific, 2025)
It is proposed that confinement in QCD be analyzed analogously with the trapping of matter inside a black hole. To this end, we compare the effective gravitational actions (including quantum corrections) with the QCD action under the assumption of instanton dominance. The similarities between the two actions are discussed, and while the analogy is formal, given the vastly different nature of the systems it establishes interesting formulas that may shed light on long-standing problems from a new perspective. © 2025 World Scientific Publishing Company.